Identification of FLRT2 as a key prognostic gene through a comprehensive analysis of TMB and IRGPs in BLCA patients - Tao, Yaling; Yu, Xiaoling; Cong, Huaiwei; Li, Jinpeng; Zhu, Junqi; Ding, Huaxin; Chen, Qian; Cai, Ting (Frontiers in Oncology, 2024)
The tumor immune environment and immune-related genes are instrumental in the development, progression, and prognosis of bladder cancer (BLCA). This study sought to pinpoint key immunerelated genes influencing BLCA prognosis and decipher their mechanisms of action. We analyzed differentially expressed genes (DEGs) between high-and low-TMB groups. Subsequently, we constructed a reliable prognostic model based on immune-related gene pairs (IRGPs) and analyzed DEGs between high-and low-risk groups. A total of 22 shared DEGs were identified across differential TMB and IRGPs-derived risk groups in BLCA patients. Through univariate Cox and multivariate Cox analyses, we highlighted five genes -FLRT2, NTRK2, CYTL1, ZNF683, PRSS41 -significantly correlated with BLCA patient prognosis. Notably, the FLRT2 gene emerged as an independent prognostic factor for BLCA, impacting patient prognosis via modulation of macrophage infiltration in immune microenvironment. Further investigation spotlighted methylation sites -cg25120290, cg02305242, and cg01832662 -as key regulators of FLRT2 expression. These findings identified pivotal prognostic genes in BLCA and illuminated the intricate mechanisms dictating patient prognosis. This study not only presents a novel prognostic marker but also carves out potential avenues for immunotherapy and targeted therapeutic strategies in BLCA. By demystifying the profound impact of immune-related genes and the tumor immune environment, this study augments the comprehension and prognostic management of bladder cancer.